Euronews as a Tool for the Formation of Europe’s Image - Yuliana Melkumyan; Karine Harutyunyan (Journal of Political Science: Bulletin of Yerevan University, 2023)
The ongoing political and economic transformations affect the image of Europe: the economic crisis, Brexit, the migration crisis, the Russian-Ukrainian war and other events are a challenge to the image of Europe. Euronews, being Europe’s leading TV channel, is used as a tool to shape Europe’s image by demonstrating European democracy, unity, identity and values.